A performance-based service life design method for reinforced concrete structures under chloride environment. (15th October 2016) - Yang, Dong-Hui; Li, Guo-Ping; Yi, Ting-Hua; Li, Hong-Nan
Highlights: The Performance-based design process can ensure a target performance level. A partial factor formula is deduced for verification of chloride-induced corrosion. Cover depth is always the dominant factor affecting chloride-induced steel corrosion. Accurate estimation of CVs is necessary for chloride-induced corrosion protection. Abstract: The chloride-induced reinforcement steel corrosion usually causes premature failure of performance in reinforced concrete structures subjected to chloride environment. However, conventional prescriptive design methods or fully probabilistic methods cannot ensure an explicit performance in design stage. The main objective of this study is to develop a performance-based service life design method, by which concrete structures such as bridges can be designed according to a predefined performance level to satisfy the target service life, reliability and deterioration level. The mechanism of chloride-induced reinforcement steel corrosion initiation was analyzed to deduce a time-varying limit state function, and the corresponding stochastic model was developed considering the effects of random factors. Through first-order reliability method, a partial factor formula was deduced to realize performance verification in performance-based design process. Finally, a case study of a concrete bridge deck exposed to marine environment was presented and the sensitivity analysis of steel corrosion was carried out. The proposed performance-based design method can rationally deal with the uncertainties of random parameters and ensure the predefined target performance to be satisfied during design process instead of predicting performance after design.